(untitled) (Journal of Hama University, 2024)
This study was conducted on ( 24 ) adult rabbits, and aimed to know the effect of different concentrations of sulfaquinoxaline ( 50-100 ) mg/kg on the kidney tissue of rabbits. ( 4 ) groups were used, where each group included (6) rabbits, the first group was left. As a natural control, while the other groups were dosed with sulfaquinoxaline, the first group was given food and water only (control), while the second group was given sulfaquinoxaline at a dose of ( 50 ) mg/kg, the third group was given a dose of ( 100 ) mg/kg of sulfaquinoxaline, and the fourth group was given a dose of ( 100 ) mg/kg of sulfaquinoxaline, then an oral dose of sodium bicarbonate for two consecutive days at a dose of ( 100 ) mg/kg of body weight. The results showed the presence of histological changes represented by the presence of expansion of Bowman’s capsule, and atrophy of the glomeruli, in rabbits treated with different doses of sulfaquinoxaline ( 100-50 ) mg / kg body weight, compared with the control group.